APLIKASI ELEKTROKOAGULASI DALAM PENGOLAHAN LIMBAH CAIR PABRIK KELAPA SAWIT - Farida Hanum; Rondang Tambun; M. Yusuf Ritonga; William Wardhana Kasim (Talenta Publisher (Universitas Sumatera Utara), 2015)
The production of crude palm oil (CPO) in Indonesia is keep increasing that make the amount of wastewater generated. Technology of anaerobic fixed bed (RANUT) have been developed, but the characteristic of the wastewater effluent of RANUT has not meet the quality standard that required by the goverment especially for COD. Because of that need to make a furhter research about the treatment of palm oil mill from the fixed bed reactor (RANUT) with electrocoagulation technique. Electrocoagulation is a process of coagulation by using a direct current through an electrochemical events are symptoms of electrolyte decomposition. This study aims to determine the effect of voltage on the adapter parameters on the performance of the electrocoagulation system and determine the best time for treatment of palm oil mill effluent. Type of electrode material used is aluminum, waste retention time 1 hour, 5 cm distance between the electrodes, a strong current of 5 amperes, voltage variations adapter 3, 4, and 5 volts. The results showed that the best results are obtained at a voltage of 5 volts for COD removal 81.32% with a value 233.5 mg/l at 180 minutes of processing time, it indicates that the processed waste has met quality standards for mill effluent COD is 350 mg/l. The highest turbidity removal percentage is obtained at a voltage of 5 volts and at a time of 180 minutes with the acquisition of 95.08%.